Test Results of a Polymer Radiator of MTZ-80 Tractor Cooling System - O. N. Didmanidze; R. T. Khakimov; E. P. Parlyuk; N. A. Bol’shakov (Сельскохозяйственные машины и технологии)
Global car manufacturers wish to increase the number of manufactured products, reduce their cost and labor input. The choice of research areas, design and technological developments in radiator construction is an extremely important and urgent task, due to the mass production of radiators for tractors and automobiles on the one hand, and the favorable development prospects of these interrelated industries, on the other. (Research purpose) To substantiate theoretically and experimentally the use of a combined cooling system containing both aluminum and polymeric water radiators and similarly liquid-oil heat exchangers based on the four principles listed above on automobiles and tractors. (Materials and methods) The authors performed bench tests using a special wind tunnel to study the thermal and aerodynamic characteristics of a prototype tractor radiator with a polyurethane core. After reaching the steady-state operating mode of the installation, the experimental values were determined for the control and measuring instruments. (Results and discussion) The authors carried out measurements of all parameters of both coolants in series at each steady-state operating mode of the bench. They obtained the main indicators dependences (reduced heat transfer, aerodynamic and hydraulic drag) of the heat exchanger, close to the operating conditions of the vehicles. (Conclusions) A prototype MTZ-80 radiator with a polyurethane core has great prospects as a future alternative radiator. An increase by 10-15 percent in the radiator heat transfer is possible by using aluminum fi ns on the surface of the polyurethane plate. A 15-20 percent reduction in hydrodynamic resistance is achieved by increasing the diameter of the capillary throughput in a polyurethane plate and the number of plates themselves in the radiator cell.